CT-guided microcoil VATS resection of lung nodules: a single-centre experience and review of the literature - Donahoe, Laura L.; Nguyen, Elsie T.; Chung, Tae-Bong; Kha, Lan-Chau; Cypel, Marcelo; Darling, Gail E.; Perrot, Marc de; Keshavjee, Shaf; Pierre, Andrew F.; Waddell, Thomas K.; Yasufuku, Kazuhiro (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Background: Video-assisted thoracoscopic surgery (VATS) is standard of care for small lung resections at many centres. Computed tomography (CT)-guided insertion of microcoils can aid surgeons in performing VATS resections for non-palpable lung nodules deep to the lung surface. Methods: Retrospective analysis of CT-guided microcoil insertions prior to VATS lung resection at a single institution from October 2008 to January 2014. Results: A total of 63 patients were included (37% male, mean age 61.6±11.4 years). Forty-two patients (67%) had a history of smoking, with 10 current smokers. Sixty one (97%) patients underwent wedge resection and 3 (5%) patients had segmentectomy. Three (5%) patients required intra-operative staple line re-resection for positive or close margins. Eleven (17%) patients had a completion lobectomy, 5 of which were during the same anaesthetic. The average time between the CT-guided insertion and start of operation was 136.6±89.0 min, and average operative time was 84.0±53.3 min. The intra-operative complication rate was 5% (n=3), including 1 episode of hemoptysis, and 2 conversions to thoracotomy. The post-operative complication rate was 8% (5 patients), and included 2 air leaks, 1 hemothorax (drop in hemoglobin), 1 post chest tube removal pneumothorax, and one venous infarction of the lingula after lingula-sparing lobectomy requiring completion lobectomy. . Average post-operative length of stay was 2.2 days. A diagnosis was made for all patients. Conclusions: CT-guided microcoil insertion followed by VATS lobectomy is safe, with short operative times, short length of stay and 100% diagnosis of small pulmonary nodules. This technique will become more important in the future with increasing numbers of small nodules detected on CT as part of lung cancer screening programs.